Siwak as a Prophetic and Evidence-Based Oral Hygiene Tool: A Qualitative Study among Islamic Scholars - Haslinda Ramli; Shahida Mohd Said; Ahmad Munawar Ismail; Tuti Ningseh Mohd Dom (Penerbit Universiti Kebangsaan Malaysia, 2024)
Vol 45, No 2